Analisis Sosial–Ekonomi Pengelolaan Hutan Kemiri Rakyat Di Kabupaten Maros (Socio–Economic Analysis of Community Candlenut Forest Management in Maros Regency) - Supratman; Irlan; Emban Ibnurusyd Mas'ud; Adrayanti Sabar; Ardian Halis; Fachrul Aslam (Fakultas Kehutanan, Universitas Hasanuddin, 2021)
enormous benefits from an economic, social, and environmental perspective. This contribution was inversely proportional to the trend of changes in the area of HKR, which had decreased. The reduction in the area of HKR was closely related to the socio-economic conditions of the farmers. The purpose of this study is to conduct a socio-economic analysis of HKR management in Maros. This research was conducted in the community candlenut forest area in Maros Regency, including villages with community candlenut forest, including Labuaja, Laiya, Limapoccoe, Rompegading, and Cenrana Baru. This study indicated that there had been a change in the community's social and economic activities in managing the candlenut forest in Maros. Communities tended to focus their livelihoods on cocoa and coffee commodities meanwhile reduce land use for candlenut. The change above is evidenced by the value of community dependence on the candlenut commodity of 35.09%.